Ru(II)-catalyzed C-H activation/alkylation of 3-formylbenzofurans with conjugated olefins: product divergence - Srinivas, Kolluru; Siddiqui, Shaziyaparveen K.; Mudaliar, Jyothi K.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
Ru-catalyzed alkylation of 3-formylbenzofuran with acrylates and acrylamides has been described. Branched selectivity with unsubstituted or beta-substituted acrylates/ acrylamides and linear selectivity with alpha-substituted acrylates have been observed. However, in all of the cases, the intermediate alkylation products seem to undergo further reactions, either cycloannulation or deformylation, depending on the substrate employed. For example, with methyl acrylate, the intermediate branched alkylation product underwent cycloannulation with another molecule of methyl acrylate, resulting in a densely functionalized cyclohexene ring formation. On the other hand, in the case of N-monosubstituted acrylamides, the branched alkylation proceeded with intramolecular aldehyde-amide condensation, leading to pyridin-2-one ring annulation. However, with both methacrylate and crotonate, deformylation of the initially formed alkylation products was observed.